2010
DOI: 10.1017/s0022215110002604
|View full text |Cite
|
Sign up to set email alerts
|

Association of age-related macular degeneration with age-related hearing loss

Abstract: Age-related hearing loss is more common in patients with age-related macular degeneration. Such patients should be questioned regarding hearing difficulty, and referred to an otolaryngologist if appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Concerning SNHL and ocular diseases, age-related SNHL has been reported with a higher occurrence rate in those with age-related macular degeneration [34], while optic neuropathy and SNHL presented with same gene defect [35]. However, few studies have focused on the correlation between glaucoma and SNHL.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning SNHL and ocular diseases, age-related SNHL has been reported with a higher occurrence rate in those with age-related macular degeneration [34], while optic neuropathy and SNHL presented with same gene defect [35]. However, few studies have focused on the correlation between glaucoma and SNHL.…”
Section: Discussionmentioning
confidence: 99%
“…Few previous studies have shown this significant association between ARMD and hearing impairment. [ 27 29 30 ] We also outlined the hypothesis of possible similar roles for melanin in development of these two disorders in the retina and inner ear. Moreover, subjective signs of hearing impairment in ARMD patients were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…They also did not explain the mechanisms by which late ARMD and hearing impairment may theoretically be associated. [ 27 32 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bozkurt et al reported recently that age-related hearing loss is more common in patients with AMD who are aged 50 years or older. AMD and age-related hearing loss share common underlying chronological and biological aging and/or disease processes, possibly because of common genetic, environmental, or lifestyle factors (e.g., exposure to oxidative stress, atherosclerosis, high cholesterol levels, or a history of heavy drinking, smoking, or occupational exposure to noise) (Bozkurt et al, 2011). It was also reported recently that gadolinium contrast agents injected intravenously appeared in the affected inner ear on magnetic resonance imaging (Yoshida et al, 2008), suggesting that disruption of the blood-labyrinth barrier or increased permeability of blood vessels in the inner ear, which is associated with the inflammatory response, is found in one-third of patients with SSNHL.…”
Section: Introductionmentioning
confidence: 99%